1982
DOI: 10.1136/oem.39.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Further follow-up study of workers from an asbestos cement factory.

Abstract: A further follow-up traced 1970 workers employed at an asbestos cement factory for at least six months between 1936 and 1977. At the beginning of this period some crocidolite was used in the factory but by the end of 1936 chrysotile had become the only type of asbestos in use. Only 378 women were employed during the period concerned, and of the 30 who had died, none had a cause of death that is generally associated with exposure to asbestos. The mortality experience of the men was examined separately for all w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…In the Norwegian study no case of mesothelioma was found among those with less than 5 years of employment. Nor was any increased risk of malignant mesothelioma found in other studies in which chrysotile asbestos was used in production (4)(5)(6). In a study from Canada (21), the asbestos-cement board production workers used chrysotile only, while another group of workers produced pipes with crocidolite in addition to chrysotile.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the Norwegian study no case of mesothelioma was found among those with less than 5 years of employment. Nor was any increased risk of malignant mesothelioma found in other studies in which chrysotile asbestos was used in production (4)(5)(6). In a study from Canada (21), the asbestos-cement board production workers used chrysotile only, while another group of workers produced pipes with crocidolite in addition to chrysotile.…”
Section: Discussionmentioning
confidence: 84%
“…A mortality study from Wales found no excess risk of respiratory cancer death among asbestoscement workers employed after 1936 (4). Also from other countries, like Sweden, England, Austria, and Belgium, no elevated risk of mesothelioma or lung cancer has been reported (5)(6)(7)(8), and some studies have even indicated a lower mortality from lung cancer in the asbestos-cement industry than in other industries in which asbestos has been handled (9).…”
mentioning
confidence: 99%
“…On the other hand, there are claims that even low doses of asbestos can increase the risk (20,30,31,34,44,(47)(48)(49)(50)(51). In several studies, it has been shown that exposure to a low dose of pure chrysotile (less than 20 fiberyears) causes no measurable increase in lung cancer (25,(52)(53)(54)(55).…”
Section: The "Threshold Value "mentioning
confidence: 99%
“…Also in other countries, chrysotile has dominated in asbestos-cement products, and many studies of asbestos-cement workers report negative results (5)(6)(7)(8). A Swedish study, however, reported elevated risk for pleural mesothelioma among asbestos-cement workers with predominantly chrysotile exposure (17), but also in the Swedish study exposure to amphiboles may have occurred in all cases.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…In several cohort studies of asbestos-cement workers, no elevated mortality from lung cancer or malignant mesothelioma was found (5)(6)(7)(8). The authors' main explanation for the lack of excess cancer risk was the predominant use of chrysotile in the production process.…”
mentioning
confidence: 99%